'The evil of our collective soul': Zombies, medical capitalism and environmental apocalypse. Issue 1 (1st March 2021) - Hughes, William
Though frequently comprehended as a vehicle for social satire or post-cultural speculation, zombie fictions also demonstrably mobilize the climatic unease of the current Anthropocene. Focusing in particular upon Max Brooks's 2006 novel World War Z: An Oral History of the Zombie War, this article considers the complex politics which have frequently underwritten a mythical origin for pandemics in the Othered East, and their contemporary reproduction in western concerns regarding unregulated surgery and the capitalism of human tissue. The article then proposes that the deterioration of human culture consequent upon the fictional zombie pandemic interrogates the contemporary understanding of integrated nationhood and problematizes the dichotomy structured between geographically stable and refugee populations. The sudden eclipse of the competitive Anthropocene by a mindless Zombicene brings not renewal for a planet no longer supporting agriculture and industry but rather a hastening of perceived environmental collapse, where unregulated hunting and the uncontrolled burning of natural resources accelerate climatic deterioration, imperilling further the survival of residual humanity. As a type of apocalyptic fiction, the zombie narrative thus poses questions with regard to the persistence of conventional human behaviours, even in a post-capitalist environment, where the political concepts structuring nationhood have come to function as little more than a memory.